The Census of David and the Problem of Causation: Divine Sovereignty, Śāṭān, and Human Responsibility - Moses Adeleke Adeoye (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2026)
The cause of a long interpretive problem, with incitement of the census attributed to the LORD in 2 Samuel chapter 24:1, and with incitement of the census attributable to the incitement of the LORD in 1 Chronicles chapter. These attributional differences have spawned an assortment of academic interpretations, such as redactional revision, theological development, historiographical reinterpretation, and canonical methods of biblical causation. The paper re-establishes the relationship of the two texts through the qualitative, textual discussion, which involves literary comparison, linguistic examination of the Hebrew word śataan, and the discussion of biblical structures of mediated agency on a larger scale. Particular attention is focused on those tales in which Godly purposes are fulfilled by secondary participants, like Job 1192, 1 Kings 22:1923 and the hardening traditions of the Exodus. The article argues that the two census accounts do not necessarily need to be viewed as mutually exclusive accounts, but they can be understood as indicating different levels of causation in the biblical narrative discourse: divine sovereignty as ultimate causation, an adversarial agent as proximate causation and David as the agent of moral responsibility. This suggestion is considered in conjunction with historical-critical interpretations, which see Chronicles as a theological reworking of Samuel. The analysis also suggests that the census was not inherently illicit in itself; the census itself is mentioned elsewhere in the Hebrew Bible as a legitimate event under justifiable circumstances, but it was guilty of intent, covenantal fidelity and royal responsibility. The article provides a constructive interpretation of these passages by placing the texts in broader biblical notions of agency, judgment and accountability, as well as current debates over inner-biblical interpretation, divine agency and the theological rationale of parallel narratives.